Innovations in the “Smart Silver Economy”: An Overview of Their Selected Strengths and Weaknesses from an Ageing Policy Perspective - Klimczuk, Andrzej (Magyar Gerontológia, 2024)
The paper aims to critically present the features of two selected ideas from the field of public policy on ageing. Namely, the concept of the “silver economy” as an economic system associated with population ageing and its more recent version, referred to the “smart silver economy”, will be discussed.